Three-level thoracolumbar vertebroplasty with screw-rod-wire construct in Kummels disease patient with neurological deficit after low impact injury - Farid Yudoyono; Ivanmorl Ruspanah; Hasan Baraqbah (Indoscholar, 2020)
Kummel disease (KD) or avascular necrosis is characterized by osteonecrosis of the vertebrae which often occurs in the thoracic area with compression fractures, intravertebral vacuum clefts, change in posture to kyphotic within months to years after minor trauma. KD is a rare disease but its incidence continues to increase with age and osteoporosis increases. Fixation of unstable thoracic fractures using the transpedicular pedicle screw (TPS) has been accepted as a procedure performed by experts. However, TPS itself has several complications combination with vertebroplasty and wire can reduce the incidence of the misplaced screw.